Influence of WAAM-CMT deposition parameters on wall geometry - Novelino, André Luiz Brito (2022)
The Wire and Arc Additive Manufacturing has called attention due to its potential in allowing the buildup of high integrity metallic parts using the commonly available welding robots in the industry. However, such a technology still presents some challenges, mainly related to obtaining optimal deposition parameters, which result in consistent layer geometry which leads to the robot and the welding power source programming. In this sense, the objective of this work is to analyze the influence of the parameters in bead and multi-layer wall geometries fabricated by the Cold Metal Transfer process to select the configurations that result in the best deposition control. The study was carried out in four steps: (i) deposition of single beads on plate, varying wire feed speed and travel speed that would result in stable and sound beads; (ii) deposition of five layer walls, considering both unidirectional and bidirectional path strategies, with and without stops between layers; (iii) deposition of ten and twenty layer walls, refining deposition parameters; and (iv) deposition of a one hundred layer wall, with the best parameter configuration among the previously tested, with bidirectional continuous strategy. The results showed that the geometry produced with a mean current of 62 A and torch travel speed of 8 mm/s along each layer and 24 mm/s on the transition between layers generated the best results, considering the natural cooling conditions. Also, the bidirectional path deposition presented the most regular geometries, when compared to the unidirectional strategy.